Analysis of Airport PAS Service Quality at the Juanda Region III Airport Authority Office - Hairunnisah, Hairunnisah; Istiyani, Yuniar (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Region III Airport Authority Office is one of the government agencies that provides public services to the community, namely airport pass services, to improve the quality of its services. The aim of this research is to find out the quality of airport fitting services provided by the Region III Airport Authority Office. The research method used is qualitative. The data sources obtained are primary data and secondary data with data collection techniques that interview five airport pass employees and five airport pass service users. One of the employees who must be interviewed is the recipient's treasurer, carrying out documentation and direct observation in the office. Region III Airport Authority. The results of this research show that the quality of airport pass services has increased as evidenced by the SKM results which continue to increase from 2021 to 2023 and changes to the airport pass service system which are very good from surveys given by airport pass users.